MULTICULUTRAL EDUCATION IN REINFORCING NATIONAL CHARACTER IN GLOBALITATION - Agung Kurniawan (Jurnal Ilmu Sosial dan Humaniora, 2018)
This study aims to determine the multicultural education in strengthening the national character in the global era. This study is a descriptive-qualitative research. The focus is on the overall depiction of multicultural education. findings in this study indicate that multicultural education in the global era Nowadays the concept of multicultural education emphasis cored internalization and characterization efforts tolerance for differences of religion, race, ethnicity, and other customary among learners is needed. The reason, the condition of the nation's current situation is not completely free from the threat of ethnic and religious conflicts, religious radicalism, separatism and disintegration. Emerging multicultural education in Indonesia is directed so that all nations may enter into an entity called educational institutions, regardless of the poor, the rich, the aristocracy, students, and so on. Multiculturalism teaches more than ensure that the learners in a class or school to learn from a variety of backgrounds